To find \((f \circ g)(x)\) which is the composition of functions \(f\) and \(g\), we will substitute \(g(x)\) into \(f(x)\).
We are given:
- \(f(x) = 10x - 6\)
- \(g(x) = 7 - 2x\)
Now we compute \((f \circ g)(x)\):
\[ (f \circ g)(x) = f(g(x)) = f(7 - 2x) \]
Now, we substitute \(7 - 2x\) into \(f(x)\):
\[ f(7 - 2x) = 10(7 - 2x) - 6 \]
Now, simplify:
\[ = 10 \cdot 7 - 10 \cdot 2x - 6 \] \[ = 70 - 20x - 6 \] \[ = 64 - 20x \]
So, \[ (f \circ g)(x) = 64 - 20x \]
Now, let's find \((g \circ f)(x)\):
\[ (g \circ f)(x) = g(f(x)) = g(10x - 6) \]
Substituting \(10x - 6\) into \(g(x)\):
\[ g(10x - 6) = 7 - 2(10x - 6) \]
Now, simplify:
\[ = 7 - 20x + 12 \] \[ = 19 - 20x \]
So, \[ (g \circ f)(x) = 19 - 20x \]
In summary, the results are:
- \((f \circ g)(x) = 64 - 20x\)
- \((g \circ f)(x) = 19 - 20x\)